Circulating Tumor Cells in Desmoid Tumors: New Perspectives - Braun, Alexcia C.; Campos, Fernando A. B.; Abdallah, Emne A.; Ruano, Anna P. C.; Medina, Tiago da S.; Tariki, Milena S.; Pinto, Fabio F. E.; de Mello, Celso A. L.; Chinen, Ludmilla T. D. (Frontiers in Oncology, 2021)
Introduction: Desmoid tumor (DT) is a rare neoplasm with high local recurrence rates, composed of fibroblastic cells that are characterized by the expression of key molecules, including the intermediate filament vimentin, Cyclooxygenase-2 (COX-2), and nuclear β-catenin; and lack of epithelial markers. Circulating tumor cells (CTCs) isolated from peripheral blood of patients with sarcomas and other neoplasms can be used as early biomarkers of tumor invasion and dissemination. Moreover, CTCs can also re-colonize their tumors of origin through a process of “tumor self-seeding.” Objectives: We aimed to identify CTCs in the peripheral blood of patients with DT and evaluate their expression of β-catenin, Transforming Growth Factor Receptor I (TGF-βRI), COX-2, and vimentin proteins. Material and methods: We conducted a prospective study of patients with initial diagnosis or relapsed DT with measurable disease. Blood samples from each patient were processed and filtered by ISET®(Rarecells, France) for CTC isolation and quantification. The CTC expression of β-catenin, COX-2, TGF-βRI and vimentin was analyzed by immunocytochemistry (ICC). Results: A total of 18 patients was included, and all had detectable CTCs. We found a concordance of β-catenin expression in both CTCs and primary tumors in 42.8% (6/14) of cases by using ICC and immunohistochemistry, respectively. Conclusions: Our study identified a high prevalence of CTCs in DT patients. Concordance of β-catenin expression between primary tumor and CTCs brings new perspectives to assess the dynamics of CTCs in the blood compartment, opening new avenues for studying the biology and behavior of DT. In addition, these results open the possibility of using CTCs to predict DT dynamics at the time of disease progression and treatment. Further studies with larger sample sizes are needed to validate our findings.